Dampak Gaya Kepemimpinan dan Motivasi Kerja Terhadap Kinerja Karyawan - Wahsya, Wahsya; Andi Sapada, Achmad Faisal; Nur, Irawati; Lukman, Siti Diva Syarifah (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to determine whether leadership style and work motivation partially and simultaneously affect the performance of employees of PT Yamaha Suracojaya Sidrap. Data collection techniques used in this study are observation, interviews, questionnaires, and documentation. With the population being all employees at PT Yamaha Suracojaya Sidrap. In order for this research to be precise and proportional, in this study saturated sampling was used where population members were sampled. Thus the number of samples in this study were 39 people. The results of this study indicate that (1) the Leadership Style variable (X1) has a partial effect on employee performance at PT. Yamaha Suracojaya Sidrap with tcount> ttable (5.595> 2.028) and significant <0.05 (0.000 <0.05). (2) The Work Motivation variable (X2) has no partial effect on employee performance at PT Yamaha Suracojaya Sidrap with the results of tcount < ttable (1.341 < 2.028) and significant> 0.05 (0.188> 0.05). (3) Leadership Style and Work Motivation simultaneously affect employee performance at PT. Yamaha Suracojaya Sidrap with Fcount> Ftable (19.735> 3.28) and significant <0.05 (0.000 <0.05). (4) The value of R2 = 0.654 means that the influence of the variables of Leadership Style (X1) and Work Motivation (X2) on Employee Performance (Y) is 65.4%. While the remaining 34.6% is influenced by other variables not included in this study such as leadership, reward, workload, ability, etc.